PERANCANGAN WEBCOMIC “QUEEN OF BEE” MENGENAI FENOMENA SOCIAL CLIMBER UNTUK REMAJA - Mifta fauziah; dini faisal (DEKAVE : Jurnal Desain Komunikasi Visual, 2020)
The behavior of teenagers today is very much influenced by the existence of social media. The desire to appear existent and get recognition makes teenagers like to show off a luxurious lifestyle and hits, even though sometimes that lifestyle is not in accordance with their real life. This is what causes a social climber phenomenon where an individual tries to do certain things in order to increase the degree of his social status. Social climber has many negative impacts on teenagers' lives. Because it requires a media to deliver information that can provide knowledge to adolescents about the social climber phenomenon and its negative impact on adolescents. The media for delivering information that will be used is in the form of webcomics or digital comics.Webcomic is used as the main media because it has an attractive appearance, is not boring and easy to access. By using a character approach that suits young social media users, the target audience will certainly be more interested. This webcomic will be supported by several media that can help promote products such as promotional videos, posters. X banner, T-shirt, key chain and instagram.The design methodology used is the Glassbox design method which consists of 4 stages, preparation, incubation, illumination and verification and the 5W + 2H data analysis method which is used as a basic concept for problem solving, that is what (what), who (who), when (when) , where (where), why (why), how (how) and how much (how much).Keywords: Webcomic, Digital Comic, Webtoon, Social Climber, Pansos, Panjat Sosial.